2011
DOI: 10.4103/0973-1482.82943
|View full text |Cite
|
Sign up to set email alerts
|

High-grade plasmablastic neoplasm of humerus in an HIV-negative patient, which was indeterminate between plasmablastic lymphoma and plasmablastic myeloma

Abstract: Plasmablastic lymphoma (PBL) of bone is a rare neoplasm that shares many confusing cytomorphological and immunohistochemical features with plasmablastic plasma cell myeloma (PBPCM). A 47-year-old female patient presented with a bony swelling and bone pain in the left humerus for the last 6 months. On radiological examination (x-ray and computed tomography) it appeared to be a lytic lesion, and a pathological fracture was detected. The patient was HIV-negative. Fine needle aspiration (FNA) was done from the les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…PBL is said to account for 2.6% of all HIV‐associated non‐Hodgkin's lymphoma. Few cases have been reported in the absence of HIV infection or immunosuppression, and only four cases of PBL of the maxillary sinus have ever been reported in immunocompetent patients. We believe that this case constitutes the fifth case of immunocompetent maxillary sinus PBL, and the first of its kind to initially present in general dental practice.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…PBL is said to account for 2.6% of all HIV‐associated non‐Hodgkin's lymphoma. Few cases have been reported in the absence of HIV infection or immunosuppression, and only four cases of PBL of the maxillary sinus have ever been reported in immunocompetent patients. We believe that this case constitutes the fifth case of immunocompetent maxillary sinus PBL, and the first of its kind to initially present in general dental practice.…”
Section: Discussionmentioning
confidence: 77%
“…Since then, many cases of HIV‐negative PBL have been reported in various oral and extra‐oral locations, with most occurring in the post‐transplant setting and in other immunocompromised states. Only a very small subset of cases of PBL has been reported in immunocompetent patients. To our knowledge, only four cases of PBL of the maxillary sinus have ever been reported in immunocompetent individuals.…”
Section: Introductionmentioning
confidence: 89%
“…CT images of the current case showed that among the bone lesions the 1 in mandible was osteoblastic whereas the other 3 were osteolytic. In the reported cases of PBL either the lesions themselves have osteolytic appearance on CT scan [ 21 23 ] or there was CT evidence of osteolysis adjacent to soft tissue lesions. [ 6 , 21 , 22 , 24 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…e morpholgy along with the immunohistochemical negativity CK20, CK7 and TTF-1 (thyroid transcription factor 1) excluded osteosarcoma and metastatic carcinoma. e morphological features of the tumor cells raised the possibility of a neuroendocrine tumor but with the NSE, chromogranin and sinaptophysin negativity it was [11] 1992 Germany 6 cases Arredondo J et al [12] 1999 USA 1 case Neben K et al [13] 2001 Germany 1 case Moazzam N et al [14] 2002 USA 1 case Stemberga V et al [15] 2003 Croatia 1 case Robinson Det al [16] 2003 Israel 1 case Bralić M et al [17] 2008 Croatia 1 case Wong T et al [18] 2008 Taiwan 1 case Marotta D et al [19] 2008 Italy 1 case Mondal SK et al [20] 2011 India 1 case Li ZS et al [21] 2011 China 1 case Caporale MF et al [9] 2013 Italy 1 case Mondello P et al [3] 2014 Italy 1 case Ben Salah H et al [22] Primary bone lymphoma is a rare entity. e patient sometimes complain about local pain, with swelling of the region.…”
Section: Discussion E Clinical Presentation Of This Case Was Initially a Tumor Of The Humerusmentioning
confidence: 99%